Ectomesenchymal Chondromyxoid Tumor: A Rare Association With an Asymmetrical Soft Palate Cleft. (July 2022) - Naidoo, Sharan; Roode, Gieljam J.; Bütow, Kurt W.; Meer, Shabnum
Ectomesenchymal chondromyxoid tumor (ECT) is a rare oral lesion first described bySmith et al. in 1995 . These tumors are typically painless, slow growing and benign masses occurring predominantly on the anterior tongue dorsum. Prior to this seminal report, many ECTs may have been misdiagnosed due to the histological similarities with other lesions. Immunohistochemical stains aid in definitive diagnosis of an ECT. A total of 39 papers since published have reported 96 patients with ECT. Most lesions involve the anterior aspect of the tongue, with only 6 occurring in the posterior tongue and 2 involving the hard palate. ECTs are considered to develop from ectomesenchymal cells of neural crest cells that have migrated to the tongue during embryological development. This paper is of a rare case of ECT of the posterolateral tongue occurring in association with an unusual asymmetrical soft palate cleft. It is postulated that since the tongue develops before the formation of the soft palate, an ECT lesion occurring on the posterior aspect may have a causal contribution to the development of the soft palate cleft.